Does PD-1 blockade play a decisive role in the pathological complete remission of unresectable MSS, BRAF V600E-mutated metastatic colorectal cancer: A case report - Tan, Li; Li, Qing-Shu; Peng, Dong; Cheng, Yong (Frontiers in Oncology, 2023)
Background Colorectal cancer (CRC) ranks third in highest incidence among human cancers. With the continuous development of anti-cancer drugs, CRC patients are treated more and more effectively. However, the treatment of patients with unresectable metastatic CRC (mCRC) remains a core point for surgeons worldwide, especially for those with microsatellite stability (MSS) and BRAF V600E mutation, who have been reported to have the worst prognosis. Case description We report a case of pathological complete remission in a patient with unresectable MSS, BRAF V600E-mutated metastatic rectal cancer after using Vemurafenib and Cetuximab in combination with Camrelizumab. Conclusions This case suggested that Vemurafenib and Cetuximab combined with Camrelizumab is effective in the treatment of MSS, BRAF V600E-mutated mCRC. To benefit more patients, further studies need to be completed.